1985
DOI: 10.1073/pnas.82.17.5690
|View full text |Cite
|
Sign up to set email alerts
|

Light regulation of the synthesis of the large subunit of ribulose-1,5-bisphosphate carboxylase in peas: Evidence for translational control

Abstract: The specific activity of ribulose-1,5-bisphosphate carboxylase (EC 4.1.1.39) increases 30-to 50-fold when dark-grown pea seedlings are shifted into the light. The large subunit (LS) of this multimeric protein is known to be synthesized in the chloroplast, but plastids from dark-grown cells contain relatively low levels of LS. However, despite the low level of LS synthesis in the plastids of dark-grown plants, these organelles contain significant levels of LS mRNA. Hybridization studies showed that the amount o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
26
0

Year Published

1986
1986
2001
2001

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(30 citation statements)
references
References 32 publications
4
26
0
Order By: Relevance
“…These data are in agreement with numerous literature reports showing leaves to contain more plastid DNA than roots (1,(14)(15)(16)(17). However, previous reports concerning plastome levels in etiolated and light grown plants have indicated that light grown shoots contain 3 to 4 times more plastid DNA than etiolated shoots of similar age (8,10). Apparently the leaves of the plant used as the explant source for the SB line are able to synthesize plastid DNA at the same rate in the presence or absence of light for at least 15 d past germination.…”
Section: Resultssupporting
confidence: 77%
“…These data are in agreement with numerous literature reports showing leaves to contain more plastid DNA than roots (1,(14)(15)(16)(17). However, previous reports concerning plastome levels in etiolated and light grown plants have indicated that light grown shoots contain 3 to 4 times more plastid DNA than etiolated shoots of similar age (8,10). Apparently the leaves of the plant used as the explant source for the SB line are able to synthesize plastid DNA at the same rate in the presence or absence of light for at least 15 d past germination.…”
Section: Resultssupporting
confidence: 77%
“…In yeast, recent evidence has demonstrated the involvement of the product of the nuclear gene PETIJI in the translational activation of mitochondrially encoded COXII transcripts (19). Translational regulation of gene expression in plants also occurs as a result of nuclear-organellar subunit interactions as is the case with ribulose-1,5-bisphosphate carboxylase (2,11). The data presented in this report suggest that some form of posttranscriptional control of the nuclear gene, Sh, may be operating under anaerobic conditions.…”
Section: Resultsmentioning
confidence: 68%
“…Inamine et al [23] suggested that light indirectly regulates large-subunit synthesis at the level of translation. As shown by our experiments phosphorylation is not involved in largesubunit translation regulation.…”
Section: Discussionmentioning
confidence: 99%